2020
DOI: 10.5194/acp-20-8123-2020
|View full text |Cite
|
Sign up to set email alerts
|

Temperature effects on optical properties and chemical composition of secondary organic aerosol derived from <i>n</i>-dodecane

Abstract: Abstract. Environmental temperature plays a vital role in controlling chemical transformations that lead to the formation of secondary organic aerosol (SOA) and ultimately impact the composition and optical properties of the aerosol particles. In this study, we investigated optical properties of n-dodecane SOA under two temperature conditions: 5 and 25 ∘C. It was shown that low-temperature conditions could enhance the real part of the refractive index (RI) of the SOA at wavelengths of 532 and 375 nm. Mass spec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 90 publications
0
11
0
Order By: Relevance
“…The experiments were conducted in a 56 m 3 (3.2 m × 6.2 m × 2.5 m) outdoor smog chamber constructed at the Chinese Research Academy of Environmental Sciences (the CRAES chamber; 40 • 02 27.73 N, 116 • 24 41.56 E). Details of the chamber have been described previously (Li et al, 2021). Briefly, the chamber was made of FEP Teflon film, the light transmission of which was above 90 % at the wavelength of 350-900 nm.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiments were conducted in a 56 m 3 (3.2 m × 6.2 m × 2.5 m) outdoor smog chamber constructed at the Chinese Research Academy of Environmental Sciences (the CRAES chamber; 40 • 02 27.73 N, 116 • 24 41.56 E). Details of the chamber have been described previously (Li et al, 2021). Briefly, the chamber was made of FEP Teflon film, the light transmission of which was above 90 % at the wavelength of 350-900 nm.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Thus particle wall loss was accounted for during the experiments. The particle growth data were corrected for wall loss, in which sizedependent coefficients from inert particle wall-loss experiments (ammonium sulfate) were applied to the particle volume data (Li et al, 2021):…”
Section: Wall-loss Correctionsmentioning
confidence: 99%
“…Li et al conducted m -xylene oxidation experiments in high relative humidity conditions (>80%), and their results showed that multiphase reactions could lead to oligomer formation, thus largely enhancing the RI value of the formed SOA. Li et al performed experiments with n -dodecane under room-temperature (25 °C) and low-temperature (5 °C) conditions and found that low-temperature conditions could promote oligomer formation and resulted in the enhancement of the scattering properties of SOA.…”
Section: Impact Of Oxidations On Physicochemical Properties Of Aerosolsmentioning
confidence: 99%
“…As an important contributor to SOA in urban areas, aromatic hydrocarbons are generally concerned about their kinetics (Atkinson and Arey, 2003;Calvert et al, 2002), reaction mechanisms (Tsiligiannis et al, 2019;J. Midey * et al, 2003;Huang et al, 2017c;Wang et al, 2020;Garmash et al, 2019), SOA yield (Cao and Jang, 2007;Kroll et al, 2007;Ng et al, 2007b;Huang et al, 2017b), ozone generation potential (Luo et al, 2019), and SOA physicochemical properties (optical properties, morphology, etc.) (Grosjean, 1981;Li et al, 2018;Li et al, 2017b;Phillips and Smith, 2014;Kim and Paulson, 2013;Huang et al, 2018).…”
mentioning
confidence: 99%
“…Long-chain alkanes, as representative substances of intermediate volatile organic compounds (IVOCs), are considered as potential contributor of SOA (Robinson et al, 2007;Trostl et al, 2016;Shiraiwa et al, 2013). The studies about long-chain alkanes includes SOA chemical compositions (Fahnestock et al, 2015;Yee et al, 2013;Aimanant and Ziemann, 2013;Yee et al, 2012), SOA yield (Loza et al, 2014;Tkacik et al, 2012), and SOA optical properties (Li et al, 2017a;Li et al, 2020), etc. The aromatic hydrocarbons and long-chain alkanes are generally studied separately in the laboratory.…”
mentioning
confidence: 99%